Performance projections : film and the body in action - Barber, Stephen, 1961- (Reaktion Books, 2014)
Performance Projections explores the dynamic relationship between film and performance, from the origins of film in Europe and the U.S. to examples in the world of contemporary digital media. Although these two forms - performance and film - have been vitally connected for more than a century, this is the first book to look with originality and depth at their intersection, particularly in relation to issues and theories of space. The rendering of performance into film has been a seminal preoccupation for both performers and film-makers. Film always does far more than document performance; it actively recreates time and space, and overhauls its rapport with the spectator's eye and body. Deploying a wide range of examples, many centred on filmic depictions of Berlin but also notably from Japanese and Chinese performance art and street cultures, this book argues that the act of filming has held the enduring power to draw distinctively performative dimensions out of unruly human gatherings, such as riots and political protests, accentuating the outlandish and aberrant aspects of performance. The book spans the special focus on performance of formative moving-image cultures to such contemporary film-making as the often-lethal camera-phone recording of snipers in Syrian cities. It proposes that the future conception of filmed performance now needs to be radically expanded in response to the transformations and flux of contemporary digital cultures. -- Publisher description.